Turbulent bubbly channel flows: Effects of soluble surfactant and viscoelasticity. (15th November 2020) - Ahmed, Zaheer; Izbassarov, Daulet; Costa, Pedro; Muradoglu, Metin; Tammisola, Outi
Highlights: Interface-resolved direct numerical simulations are performed. Combined effects of soluble surfactant and viscoelasticity are investigated. Surfactant prevents formation of bubble clusters near the wall. Viscoelasticity promotes formation of bubble clusters near the wall. Abstract: Interface-resolved direct numerical simulations are performed to examine the combined effects of soluble surfactant and viscoelasticity on the structure of a bubbly turbulent channel flow. The incompressible flow equations are solved fully coupled with the FENE-P viscoelastic model and the equations governing interfacial and bulk surfactant concentrations. The latter coupling is achieved through a non-linear equation of state which relates the surface tension to the surfactant concentration at the interface. The two-fluid Navier-Stokes equations are solved using a front-tracking method, augmented with a very efficient FFT-based pressure projection method that allows for massively parallel simulations of turbulent flows. It is found that, for the surfactant-free case, bubbles move toward the wall due to inertial lift force, resulting in formation of wall layers and a significant decrease in the flow rate. Conversely, a high-enough concentration of surfactant changes the direction of lateral migration of bubbles, i.e., the contaminated bubbles move toward the core region and spread out across the channel. When viscoelasticity is considered, viscoelastic stresses counteract the Marangoni stresses, promoting formation of bubbly wall-layers and consequently strong decrease in the flow rate. The formation of bubble wall-layers for combined case depends on the interplay of the inertial and elastic, and Marangoni forces.